Fan Blade Balancing Process on CFM56-5B Engine Airbus A320 using the Trim Balance Method - Nugroho, Dimas Augie; Caturwati, Ni Ketut (Universitas Sultan Ageng Tirtayasa, 2023)
Fan unbalance is a condition of imbalance of the fan blades with respect to the axis of play and voltage. This imbalance results in the shaft bearing receiving additional centrifugal force due to unbalanced load. This condition causes excessive vibration that produces noise. Trim Balance is a method to reduce vibration by installing balancing screws of different weights on the fan blades to achieve balanced rotation. Fan trim balance can be performed on vibration sources from FAN /LPC or from LPT as they are located in one axle, thus influencing each other. The unit of vibration measurement used is Mils which shows the maximum deviation shift distance (Displacement), with a value of 1 mils = 0.001 inch, or in microns with a value of 1 μm = 1x10-6 m. According to the Aircraft Maintenance Manual (AMM) instructions, the recommended maximum vibration limit is 2 mils, for some airlines the vibration limit is tightened to 1.0 mils. Based on ISO 20816-2 standard, the recommended vibration value is 2.5 mils, with an operating threshold of 5.3 mils. The Fan Trim Balance process begins with the engine run-up process to obtain engine vibration data. During the run-up process, the EVMU will record vibrations at N1 levels of 64%, 84%, 88%, 92%, and 96%. Once the data is collected, your EV will adjust the position and size of the balance screw, which will then be replaced at the base of the fan blades. After adjustment, the engine re-run-up to review the magnitude of the vibration. The trim balance process will be repeated until the vibration level matches the specified parameters. The ratio of vibration levels before and after the trim balance process on Engine 1 is 1.5 Mils and 0.4 Mils, with a difference of 1.1 Mils, while on Engine 2 is 1.8 Mils and 0.5 Mils, with a difference of 1.3 Mils. In this case, the Airbus A320 aircraft requires two trim balance processes to ensure that the vibration level in the engine meets the feasibility parameters.